2003
DOI: 10.1038/sj.npp.1300223
|View full text |Cite
|
Sign up to set email alerts
|

Altering Cortisol Level does not Change the Pleasurable Effects of Methamphetamine in Humans

Abstract: Preclinical studies have linked corticosteroid secretion and levels with drug self-administration by animals. In a double-blind, cross-over study, subjective, physiological, and endocrine responses to intravenous doses of methamphetamine 0.5 mg/kg or placebo were assessed in eight methamphetamine-experienced subjects after three cortisol-modifying premedication conditions: augmenting cortisol level with oral hydrocortisone 50 mg, blocking cortisol response with the corticosteroid synthesis inhibitor metyrapone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 28 publications
6
29
1
Order By: Relevance
“…Preclinical findings have shown that stress and glucocorticoids not only increase levels of mesolimbic DA but also interact with the effects of drugs of abuse on this neurotransmitter system (Barrot et al, 2001;Cho and Little, 1999;Marinelli and Piazza, 2002;Yavich and Tiihonen, 2000). Nevertheless, findings from human laboratory studies have not been consistent with those of the preclinical literature in demonstrating relationships between glucocorticoids and psychostimulant reinforcement (Alessi et al, 2003;Harris et al, 2003;Wachtel et al, 2001). Since it has been more difficult to study the neurochemical mechanisms that underlie behavioral effects of drugs in humans, the role of glucocorticoids in drug reinforcement and the relevance of the relationship between glucocorticoids and DA neurotransmission in humans remain ambiguous.…”
Section: Introductioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Preclinical findings have shown that stress and glucocorticoids not only increase levels of mesolimbic DA but also interact with the effects of drugs of abuse on this neurotransmitter system (Barrot et al, 2001;Cho and Little, 1999;Marinelli and Piazza, 2002;Yavich and Tiihonen, 2000). Nevertheless, findings from human laboratory studies have not been consistent with those of the preclinical literature in demonstrating relationships between glucocorticoids and psychostimulant reinforcement (Alessi et al, 2003;Harris et al, 2003;Wachtel et al, 2001). Since it has been more difficult to study the neurochemical mechanisms that underlie behavioral effects of drugs in humans, the role of glucocorticoids in drug reinforcement and the relevance of the relationship between glucocorticoids and DA neurotransmission in humans remain ambiguous.…”
Section: Introductioncontrasting
confidence: 47%
“…Although findings from one human laboratory study indicated that intravenous cortisol administration increased reports of craving in cocaine abusers , the majority of findings in this area of research have been negative. For example, pharmacological blockade of drug-induced increases in cortisol did not alter the subjective responses to psychostimulants in humans in several studies (Harris et al, 2003;Ward et al, 1998Ward et al, , 1999, nor did it modify patterns of cocaine self-administration in non-human primates (Broadbear et al, 1999). Furthermore, treatment with cortisol synthesis inhibitors has been reported to increase cocaine use in methadone maintained patients with a history of cocaine abuse .…”
Section: Discussionmentioning
confidence: 99%
“…Although very few studies have looked at the relationship between methamphetamine and the HPA axis, there is evidence for a methamphetamine-induced rise in plasma cortisol in humans (Besser et al 1969;Fehm et al 1984;Harris et al 2003) and plasma corticosterone in rats (Asano and Moroji 1974;Szumlinski et al 2001). Although some studies also suggested a potential role for corticosterone in the acquisition of D-amphetamine self-administration (Piazza et al 1989(Piazza et al , 1990, the HPA axis may play less of a role in the acquisition of methamphetamine self-administration (Moffett and Goeders 2005).…”
Section: Discussionmentioning
confidence: 93%
“…For example, such a lack of between-subjects correlations has previously been documented for correlations between MDMA plasma levels and autonomic effects [52]. The pleasurable effects of amphetamine and methamphetamine in humans also did not change when cortisol levels were increased pharmacologically [53] or lowered by metyrapone administration prior to methamphetamine administration [33]. As noted above, MDMA-induced elevations of mineralocorticoids may also contribute to regulation of the hypertensive effects of MDMA.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, intravenous methylphenidate at doses of 10 mg (0.12-0.15 mg/kg) or 0.3 mg/kg significantly increased cortisol levels in healthy subjects [32]. Related catecholaminergic substances, such as amphetamine and methamphetamine, have also been shown to elevate cortisol levels in some studies [33,34,35,36] but not others [14]. A single dose of the NET inhibitor reboxetine also increased cortisol levels [37], particularly in subjects who scored high on subclinical depression [38].…”
Section: Discussionmentioning
confidence: 99%